An Exceptional Adenocarcinoma in a Girl - Bangaly Traore; Ibrahima Kalil Cisse; Malick Bah; Ahmed Monzomba Keita (Case Reports in Oncological Medicine)
Anal adenocarcinoma is very rare and usually occurs in the elderly. We present a case of a 12-year-old girl with an anal margin painful tumor infiltrating the lower rectum, with perineal and vulvar permeation nodules and bilateral fixed inguinal and iliac lymph nodes. Histology showed anal adenocarcinoma with mucosecreting component and independent cells. She had no extra pelvic metastasis on CT scan. She underwent a colostomy and palliative care. This exceptional case challenges us on the diversity of forms of anal cancers that require a multidisciplinary approach. The precarious social context and the age of onset make it difficult to manage this rare cancer.